2009
DOI: 10.1109/tasc.2009.2018804
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Inclusion-Induced Critical Current Deviation of Nb/AlOx/Nb Josephson Junctions in Superconducting Integrated Circuits

Abstract: Josephson junctions with niobium electrodes connected with palladium, which is employed in the bump metallization, have about 20% larger critical current density than those with electrodes not connected with palladium. This increase in the critical current density coincides with the desorption of hydrogen from the niobium electrodes. Hydrogen incorporates during the fabrication process and desorbs in an atmosphere when the niobium surface is covered with palladium. The decrease in hydrogen concentration in nio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The normal state resistance of the junctions decays, which agrees with results reported in Refs. [8][9][10]. Furthermore, we have observed the junction size effect on R n aging behavior, similar to that, reported in Ref.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The normal state resistance of the junctions decays, which agrees with results reported in Refs. [8][9][10]. Furthermore, we have observed the junction size effect on R n aging behavior, similar to that, reported in Ref.…”
Section: Resultssupporting
confidence: 90%
“…[8][9][10]. Unusually, this R n reduction was accompanied with an increase in the subgap resistance, R j .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently found that hydrogen inclusions in Nb electrodes induce a large I c deviation. 2,3 An identical report followed confirming the influence of hydrogen inclusion in Nb films on the I c values. 4 We stated in our previous report 3 that I c changes coincide with the inclusion/exclusion of hydrogen into/from Nb electrodes, and that they are gradual and reversible.…”
Section: Introductionmentioning
confidence: 63%
“…However, a part of the Pd remained in the via holes of the CTL layer in the way we explained in our previous reports. 2,3 The Pd areas for single junction TEGs were formed on and within the Nb pads using the lift-off method. The electrical measurements could be performed without Pd removal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation